Higher level of communication between the medical staff and the performance staff is associated with a lower hamstring injury burden: a substudy on 14 teams from the UEFA Elite Club Injury Study - Ekstrand, J.; Hägglund, M.; Waldén, M.; Gauffin, H.; Baudot, C.; Biosca, P.; Braun, M.; Dittmar, K. H.; Kalogiannidis, D.; McNally, S.; Pruna, R.; Puga, N.; et al. (BMJ Open Sport & Exercise Medicine, 2025)
Objectives External risk factors connected to club, team and coaching are believed to be important in the causation of hamstring injuries, but little is known about the preventive measures used. The objective was to analyse the association between preventive factors and hamstring muscle injury burden.